Albiglutide, a weekly GLP-1 receptor agonist, improves glycemic parameters in Japanese patients with type 2 diabetes over 1 year when added to single oral antidiabetic drugs. (4th March 2017) - Okuda, Inaha; Wilson, Timothy H.; Yue, Lin; Nakajima, Hiromu; Carr, Molly C.; Tsuboi, Maho; Nino, Antonio; Seino, Yutaka
Abstract: Objective: To evaluate the safety and efficacy of once weekly albiglutide added to a single oral antidiabetic drug (OAD) in Japanese patients with inadequately controlled type 2 diabetes mellitus (T2DM). Research design and methods: In this phase 3, 1 year study (NCT01777282), patients ( N = 374) received albiglutide 30 mg plus a single OAD (sulfonylurea [ n = 120], biguanide [ n = 67)], glinide [ n = 65], thiazolidinedione [ n = 61], or α-glucosidase inhibitor [ n = 61]). Albiglutide could be increased to 50 mg after Week 4, based on glycemic criteria. Primary endpoints were the incidence of adverse events (AEs) and hypoglycemia; secondary endpoints were changes from baseline at Week 52 in HbA1c and fasting plasma glucose (FPG), proportion of patients achieving HbA1c ≤7.0%, and withdrawals due to hyperglycemia. Results: On-therapy AEs occurred in 78.6% of patients and serious AEs in 2.1%. Common AEs were nasopharyngitis (32.6%), constipation (7.2%), and diabetic retinopathy (5.3%). No serious AEs occurred more than once or were reported in >1 patient. Hypoglycemia occurred in 6.4% of patients, mostly in the albiglutide + sulfonylurea (14.2%) and the albiglutide + glinide (6.2%) groups. Albiglutide was uptitrated in 53.2% of patients. Mean baseline HbA1c was 8.1%. Mean decreases from baseline in HbA1c were observed with the addition of albiglutide to thiazolidinediones (−1.42%), α-glucosidase inhibitors (−1.39%), sulfonylureas (−1.04%), glinides (−0.95%), and biguanides (−0.94%). HbA1c of <7% in >50% of patients and mean reductions in FPG were achieved in all groups. Mean changes from baseline in body weight ranged from +0.52 kg (albiglutide + thiazolidinedione) to −0.33 kg (albiglutide + biguanide). Limitations of the study included open label treatment that was not randomized. Conclusions: When combined with a single OAD in Japanese patients with inadequately controlled T2DM, albiglutide led to favorable changes in all glycemic parameters, with minor changes in body weight depending on the background OAD. No new safety concerns were noted.